Spatial Distribution of Rainfall in the Opiyang Watershed Using the Thiessen Polygon Method and its Implications for River Discharge - Susanti Rahman; Amirudin Miradj (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Understanding the spatial distribution of rainfall is fundamental for analyzing water availability in a river basin. This study aims to examine the rainfall distribution in the Opiyang Watershed using the Thiessen Polygon Method, investigating its spatial and temporal variability, and analyzing its impact on river discharge with the F.J. Mock hydrological model. Monthly rainfall data from three stations—Mancalele, Mekarsari, and Dakaino—covering 2015–2024 were processed using Geographic Information Systems (GIS). Results show Dakaino station has the largest spatial influence, with a weight of 70.24% over an area of 172.5 km², followed by Mekarsari (17.14%, 42.1 km²) and Mancalele (12.62%, 31 km²). The annual mean rainfall recorded is 2,329 mm, with peak rainfall in June (242 mm) and the lowest in October (140 mm). Discharge simulations indicate the Q80% reliability flow ranges from 0.46 to 1.47 m³/s. A strong correlation (r = 0.87) exists between rainfall and river discharge, with rainfall explaining about 75.7% of discharge variability. This relationship provides a scientific basis for water resource management, flood mitigation, and sustainable infrastructure planning in Halmahera Timur. The Thiessen Polygon Method offers more accurate and representative estimates of the watershed’s rainfall compared to simple average methods. Practically, these findings emphasize prioritizing upstream conservation, especially Dakaino, and using a minimum Q80% of 0.46 m³/s for designing irrigation and water supply systems to ensure water availability during dry months.